Textile Sublimation Printing: GLCM Print Mottle Assessment of Black Printed Fabric - Emilija Toshikj, Bojan Prangoski (Kaunas University of Technology (Lithuania), 2023)
The white fabric was printed with different printing temperatures and pressing times using the sublimation printing process in solid-tone black color with a 100 % total ink limiting level. Non-uniformity of the print was examined through print mottle determined by grey level co-occurrence matrix (GLCM) image processing method. Color strength of print was also determined by reflectance spectrophotometry. The print with the lower print mottle was obtained at a printing temperature of 190 °C at a longer pressing time of 120 s or at an increased printing temperature of up to 210 °C at the reduced pressing time of 60 s. The print with the lower print mottle had the lowest entropy, contrast, and correlation and the highest energy and homogeneity. The print with a higher color strength was accompanied by decreased print mottle. Choosing a suitable printing temperature and pressing time for sublimation printing is helpful in achieving print with low print mottle and high color strength and balancing cost, price, and price.
Keywords: print quality, GLCM, color strength, sublimation, polyester